Tourist perception towards Malaysian street food / Mohd Arif Hafizi Mohd Asri and Nur Ashikin Azman - Mohd Asri, Mohd Arif Hafizi; Azman, Nur Ashikin (2019)
This undergraduate project was conducted to determine the perception of tourists towards Malaysia street food. Street food present the inexpensive food image. Street food also is a part of culinary culture that can give impact towards the tourist at the destination. Besides, street food also can be defined as the ready- to-eat food that sell inexpensive food. Tourist gave support to the tourism places, local economy and conversation programs by their spending which is will effect the economy. This study will need 384 respondents to gain their thoughts and opinion towards this case which is their perception towards the Malaysia street food. The method of this study is by using quantitative method which is by using questionnaire. This questionnaire will be distribute to the 400 respondents but only 384 respondents as mentioned above will be analyse where the other 16 is as backup. This research study will conduct in Pasar Seni area which is lots of tourist there because of the area is where wold the heritage, souveniers for the tourist there. By doing this study, researchers can look into the opinion of the tourist towards the street food and how they perceive towards the food.